Faktor-Faktor Penentu Indeks Pembangunan Manusia Pada Negara Asean Periode 2012-2019: Determinants Of The Human Development Index In Asean Countries For The Period 2012-2019 - Alatas, Abdullah; Amarudin, Luluk; Wibowo, Muhammad Ghafur (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The main purpose of economic development is to improve the well-being of the people, one of the indicators that reflects economic development is human development. The Human Development Index (HDI) of a region is influenced by various factors. This study aims to understand the factors that affect the Human Development Index in 6 ASEAN Countries. This research method is a quantitative approach with a panel data regression model and model estimation using the Fixed Effect Model (FEM) approach. The results of the study show that independent variables consisting of Gross Domestic Product (GDP), Population, and Government Expenditure in Education and Health have a simultaneous effect on the Human Development Index. As for partially, there are only two independent variables that have a significant positive effect, namely the Number of Population and Government Expenditure in the Field of Education, with values of 0.0002 and 0.0150, respectively, which are smaller than 5%. Meanwhile, the variables Gross National Income and Government Expenditure in the Health Sector had no effect with values of 0.9182 and 0.5596, respectively, which were greater than 5%.